Pentingnya Dukungan Keluarga Dalam Meningkatkan Kesehatan Mental Mahasiswa Prodi Bimbingan Penyuluhan Islam - Ahmad Labiq; Nashcihah Nashcihah; Siti Hulaiyah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2023)
The family is the smallest unit of society consisting of the head of the family and several people who are gathered and live in one place under one roof in a state of interdependence. This research aims to find out what things families can do for their children who are do studies at one of the UIN Syarif Hidayatullah Jakarta and how important this is. The method in this research uses qualitative methods. Qualitative data was obtained by conducting in-depth interviews and Focus Group Discussions (FGD) with several students who will become informants. The results of the research show that the conclusion of this research is families have a very important role in creating a supportive environment for the welfare of their children’s mental health. According to them, family is the best support system which has the most important role in providing full support which makes them even more enthusiastic.